First-principles calculations of structural and electronic properties of MgO and Li DOPED MgO / Dzulkhairi Tajuddin Mustaffa - Mustaffa, Dzulkhairi Tajuddin (2019)
In this research, first principles calculation in CASTEP within density functional theory framework is used to study the structural properties and electronic properties of magnesium oxide (MgO). MgO has been observed to have its electronic properties to depend on its structural parameters. This work consist of three main parts, firstly the lattice parameters dependency of MgO towards its properties, the second part is the crystallite size dependency of MgO towards its properties and the third part is the lithium doping dependency of MgO towards its properties. For the first part, the lattice parameters that will be used in the calculation were obtained experimentally via X-ray Diffraction (XRD) of MgO. MgO structure that is used in this study is the face-centered cubic structure (Fm3̅m) with space group of 225. From the calculated band structures, we have found that the decrease of MgO band gap is a consequence of the increase in lattice parameters and these findings agrees well with the experimental findings of band gap narrowing in MgO. The density of states of MgO is presented to study the shifting of the highest valence band and lowest conduction band. In the second part, the crystallite size dependency of MgO towards its structural properties and electronic properties is investigated. Two MgO structures were constructed on the basis of face centered cubic structure and the supercell method was implemented to construct MgO with 1x1x1 supercell and 2x2x2 supercell to simulate different crystallite size. From the calculations, as the crystallite size of MgO becomes smaller as simulated by MgO with 1x1x1 supercell, the lattice parameters of the MgO crystal increases. These finding proves the lattice expansion of MgO nanostructures. This lattice expansion is also the reason behind the band gap decrease of MgO which is agreeable with our findings from the first part of this work. The last part of this work is to study the doping effect of lithium in face centered cubic MgO. Initially, the stoichiometry of Li doped MgO is determined with two possibilities, which is the LixMg1-xO and Li2xMg1-xO. The MgO structures were constructed with 2x1x1 supercell which consists of eight Mg atoms and eight O atoms and one lithium atom was inserted to replace one Mg atom in the 4a Wyckoff position to simulate the LixMg1-xO and in the second structure one lithium atom is inserted to replace one Mg atom in the 4a Wyckoff position and another lithium atom in the tetrahedral site; the MgO 2x1x1 to simulate the Li2xMg1-xO structure. From the energy calculated from both structures, it is found that Li2xMg1-xO electronic structure gives more accurate illustration of Li doped MgO. Three concentration of Li doping were studied which is x=0, 0.125 and 0.25 and it is found that as the Li concentration increases, the lattice parameters of Li doped MgO increases. The band gap of Li doped MgO decreases as the Li concentration increases. The density of states of Li doped MgO shows that Li creates a new energy level in the band structures of MgO promoting the decrease of band gap. The decrease of MgO band gap makes it viable for use in various electronic devices applications.